The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.virol.2013.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic control of herpes simplex virus pathogenesis by IRF-3, and IRF-7 revealed through non-invasive bioluminescence imaging

Abstract: Interferon regulatory factors IRF-3 and IRF-7 are central to the establishment of the innate antiviral response. This study examines HSV-1 pathogenesis in IRF-3−/−, IRF-7−/− and double-deleted IRF3/7−/− (DKO) mice. Bioluminescence imaging of infection revealed that DKO mice developed visceral infection following corneal inoculation, along with increased viral burdens in all tissues relative to single knockout mice. While all DKO mice synchronously reached endpoint criteria 5 days post infection, the IRF-7−/− m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
45
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 89 publications
0
45
0
Order By: Relevance
“…Periocular disease scoring was performed as previously described and summarized here: 0, no pathology; 0.5, minor eyelid swelling; 1.0, minor eyelid and nasal swelling; 1.5, moderate eyelid and nasal swelling; 2.0, severe eyelid swelling with minor periocular hair loss and skin damage; 3.0, neurological symptoms (20).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Periocular disease scoring was performed as previously described and summarized here: 0, no pathology; 0.5, minor eyelid swelling; 1.0, minor eyelid and nasal swelling; 1.5, moderate eyelid and nasal swelling; 2.0, severe eyelid swelling with minor periocular hair loss and skin damage; 3.0, neurological symptoms (20).…”
Section: Methodsmentioning
confidence: 99%
“…An additional study showed that STING-deficient mice have increased HSV-1 titers in corneas relative to control mice, but no further parameters of pathogenesis were measured (16). These studies confirm a role for STING in HSV infection and collectively suggest that STING deficiency renders the host highly susceptible to HSV infection, equivalent perhaps to deficiencies in STAT1, type I IFN receptors, or IRF-3/7 (17)(18)(19)(20). These studies notwithstanding, how STING-driven responses shape HSV pathogenesis following peripheral challenge remains unknown.…”
mentioning
confidence: 89%
“…he type I interferon (IFN) antiviral response (IFN-␣ and IFN-␤) plays a major role in host innate immunity to RNA and DNA virus infections (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). This antiviral type I IFN response is tightly regulated, in part, by interferon regulatory factors (IRFs) via upstream signaling induction by various pattern recognition receptors (PRRs).…”
mentioning
confidence: 99%
“…To determine the possible role of IRFs in retroviral pathogenesis, B6 background mouse strains with IRF-3 Ϫ/Ϫ , IRF-7 Ϫ/Ϫ , and DKO congenic status (10,13,35) were infected with 5 ϫ 10 4 PFU of LP-BM5 retrovirus and were compared to MAIDS-susceptible B6 and MAIDS-resistant 129S1/SvImJ (129) mice (NCI, Bethesda, MD) (31,36). Upon sacrifice, at 8 weeks postinfection (wpi), MAIDS was assessed (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation